2018
DOI: 10.1038/s41598-018-28754-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GABAergic actions resulting from the coapplication of the steroid 3α-hydroxy-5α-pregnane-11,20-dione (alfaxalone) with propofol or diazepam

Abstract: Many GABAergic drugs are in clinical use as anesthetics, sedatives, or anxiolytics. We have investigated the actions of the combinations of the neuroactive steroid 3α-hydroxy-5α-pregnane-11,20-dione (alfaxalone) with the intravenous anesthetic propofol or the benzodiazepine diazepam. The goal of the study was to determine whether coapplication of alfaxalone reduces the effective doses and concentrations of propofol and diazepam. Behavioral effects of alfaxalone, propofol, diazepam, and the combinations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 50 publications
(64 reference statements)
8
24
1
Order By: Relevance
“…(Fig. ) and increases the decay time constants of sIPSCs (Cao et al ), its relative effects are similar on tonic and phasic activation of the synaptic‐type receptor and, therefore, on the ratios of relative integrated charge transfer (0.997:0.003 for tonic vs. phasic in the presence of 1 μ mol/L propofol at 0.001 Hz frequency per synapse and 0.25:0.75 at 1 Hz).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…(Fig. ) and increases the decay time constants of sIPSCs (Cao et al ), its relative effects are similar on tonic and phasic activation of the synaptic‐type receptor and, therefore, on the ratios of relative integrated charge transfer (0.997:0.003 for tonic vs. phasic in the presence of 1 μ mol/L propofol at 0.001 Hz frequency per synapse and 0.25:0.75 at 1 Hz).…”
Section: Discussionmentioning
confidence: 89%
“…For phasic activity, it is considered that during the peak synaptic response 100% of receptors are active, that is, P Open,Peak is indistinguishable from 1 (Kitamura et al ; Takahashi et al ; McDougall et al ). The decay time constants of sIPSCs are 30 msec under control conditions, and 65 or 90 msec in the presence of 0.3 or 1 μ mol/L propofol (Cao et al ). Then, the total charge transfer for a single sIPSC is 0.03, 0.065, or 0.09 P Open × s in the presence of 0, 0.3, or 1 μ mol/L propofol, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although propofol and alphaxalone interact synergistically (Cao et al, ), propofol has only weak or no selectively between Sites 1 and 2. (Chiara et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, binding to one site will allosterically enhance the affinity of the other sites, leading to the hypothesis that combinations of general anaesthetics should act synergistically if they bind selectively to distinct sites. Pioneering studies have shown that steroids interact allosterically with etomidate and propofol both in vivo and in vitro (Cao et al, ; Chen et al, ; Drexler, Balk, & Antkowiak, ). Here, using three sets of general anaesthetics that bind with high selectivity to one of the three sites shown in Figure c, we find that the potencies of combinations of site‐selective anaesthetics that bind to the same site are additive, whereas those that bind to two or three distinct sites are increasingly synergistic.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different mutations may divergently affect symmetry and/or crosstalk among anesthetic sites. Energy additivity in wild-type GABA A receptors is supported by studies of drug combinations (Shin et al, 2017;Cao et al, 2018) that notably used receptors formed from concatenated subunit assemblies. Concatenated receptors display less spontaneous activation than free subunit assemblies, and may also reduce heterogeneity in subunit arrangement (Baumann et al, 2001;Guitchounts et al, 2012).…”
Section: Discussionmentioning
confidence: 99%